Upgrading of biomass-derived bio-oil via catalytic hydrogenation with Rh and Pd catalysts. (January 2022) - He, Yifeng; Liu, Ronghou; Yellezuome, Dominic; Peng, Wanxi; Tabatabaei, Meisam
Abstract: The high oxygen content of biomass-derived bio-oil, a multi-component organic, has limited its application as liquid fuels. Oxygen removal from crude bio-oil by catalytic hydrogenation is an upgrading approach with huge potential to produce second-generation biofuels. In light of that, the present work mainly focuses on upgrading biomass-derived bio-oil via catalytic hydrogenation. Accordingly, a batch hydrogenation reactor with a catalyst basket of adjustable volume was specifically designed. Moreover, a supported Rh/ZrO2 catalyst was prepared and was studied for bio-oil upgrading, along with similar commercial catalysts. The developed Rh/ZrO2 catalyst could hydrogenate guaiacol completely, resulting in non-oxygenated hydrocarbons. The re-utilization of Rh/ZrO2 for five times led to the catalyst deactivation, with the conversion rate (Cgua ) declining to as low as 50.3 mol%. The regeneration of deactivated Rh/ZrO2 was realized through carbon deposition removal and showed a restored C gua to 92.4 mol%. The oxygen content of heavy-oil products obtained under Rh/ZrO2, Rh/Al2 O3, and Pd/Al2 O3 decreased to 28.2 wt%, 29.1 wt%, and 30.2 wt%, respectively. The catalytic groups achieved certain deoxygenation extents, with Rh/ZrO2 being ranked as the highest (58.49%). Finally, given the costly nature of noble-metal catalysts, the metal loading of Rh/ZrO2 was ten times lower, offering obvious economic advantages over its commercial counterparts. Highlights: Upgrading of biomass-derived bio-oil via catalytic hydrogenation was investigated. A novel supported Rh/ZrO2 catalyst was prepared and compared with commercial ones. Catalyst hydrogenated guaiacol completely, producing non-oxygenated hydrocarbons. Metal loading of Rh/ZrO2 was 10 times lower vs. the commercial catalysts. The developed catalyst was economically advantageous due to lower meatal loading.